2022
DOI: 10.1126/science.abl5311
|View full text |Cite
|
Sign up to set email alerts
|

Universal antigen encoding of T cell activation from high-dimensional cytokine dynamics

Abstract: Systems immunology lacks a framework with which to derive theoretical understanding from high-dimensional datasets. We combined a robotic platform with machine learning to experimentally measure and theoretically model CD8 + T cell activation. High-dimensional cytokine dynamics could be compressed onto a low-dimensional latent space in an antigen-specific manner (so-called “antigen encoding”). We used antigen encoding to model and reconstruct patterns of T cell immune activation. The mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 45 publications
1
26
0
Order By: Relevance
“…Many predictors are trained using epitopes from the Immune Epitope Database labelled with readouts from single time points 7 . However, Achar et al 75 illustrated that integrating cytokine responses over time improved prediction of quality. Antigen load and affinity can also play important roles 74 , 76 .…”
Section: Key Challengesmentioning
confidence: 99%
“…Many predictors are trained using epitopes from the Immune Epitope Database labelled with readouts from single time points 7 . However, Achar et al 75 illustrated that integrating cytokine responses over time improved prediction of quality. Antigen load and affinity can also play important roles 74 , 76 .…”
Section: Key Challengesmentioning
confidence: 99%
“…Mounting experimental evidence indicates that the TCR (as a case study for KPR) may indeed produce multiple intracellular second messengers which may enable T cells to detect antigen quantity alongside antigen quality (78)(79)(80)(81)(82). Our results lay the ground for further theoretical work aimed at the understanding the effects of noise in multi-output receptor signaling pathways (78,(83)(84)(85).…”
Section: Bmentioning
confidence: 71%
“…These outputs can be used to infer the presence of multiple ligands in a mixture (53), convey information about ligand concentration or other environmental conditions in addition to ligand identity (77), or perform other complex signaling processing tasks (78). Mounting experimental evidence indicates that the TCR (as a case study for KPR) may indeed produce multiple intracellular second messengers which may enable T cells to detect antigen quantity alongside antigen quality (78)(79)(80)(81)(82). Our results lay the ground for further theoretical work aimed at the understanding the effects of noise in multi-output receptor signaling pathways (78,(83)(84)(85).…”
Section: Bmentioning
confidence: 99%
“…tolerance, TH-1, TH-2, or TH-17 responses…). In this context, Achar et al have recently reported that distinct cellular responses of the T cells are elicited by antigenic peptides of different affinity for the OT-I TCR (Achar et al, 2022). Peptide affinity influences both the half-life of TCR-pMHC binding, and the stability of T cell/APC interactions (Moreau et al, 2012).…”
Section: Resultsmentioning
confidence: 99%